Pengaruh batang bawah terhadap pola pita isoenzim dan protein batang atas pada okulasi tanaman karet (Hevea brasiliensis Muell Arg.) The effect of root stocks on isozymes and protein partterns of scion the budgrafting of rubber plant (Hevea brasiliensis Muell Arg.) - N TORUAN-MATHIUS; . LIZAWATI; H ASWIDINNOOR; I BOERHENDY (E-Journal Menara Perkebunan, 2002)
RingkasanHeterogenitas batang bawah pada sistem okulasi Hevea brasiliensis dapat menyebabkan interaksi batang bawah dengan batang atas dapat menimbulkan berbagai tingkat keragaman respons antar individu batang atas dari klon yang sama. Tujuan penelitian ini adalah untuk mengetahui pengaruh berbagai jenis batang bawah terhadap respons batang atas dari klon karet yang sama pada okulasi, berdasarkan perubahan pola pita protein, dan isoenzim esterase (EST), asam fospatase (AP), malat dehidrogenase (MDH), fosfogluko oksaloasetat (PGD), fosfo glukosa isomerase (PGI), peroksidase (PER), sikimik dehidrogenase (SKD), glutamat oksaloasetat (GOT) dan leusin aminopeptidase (LAP) dari daun atau lateks batang atas. Kombinasi diuji adalah klon (a) batang atas klon PB260 yang dikombinasikan dengan PR255, BPM1, LCB1320, PR300, AVROS2037, RRIM712 dan GT1, sebagai kontrol GT1/GT1. (b) sebagai batang atas adalah BPM1, BPM24, RRIC100 dan RRIC102 yang dikombinasikan dengan batang bawah BPM1, BPM24, RRIC100, RRIC101, RRIC102 dan RRIC110. Hasil yang diperoleh menunjukkan adanya perubahan pola pita protein lateks PB260 yang diokulasikan pada PR255, BPM1, LCB1320, PR300, AVROS2037, RRIM712 sebagai batang bawah. BPM1, BPM24, RRIC100, RRIC102 sebagai batang atas dengan BPM1, BPM24, RRIC100, RRIC101, RRIC102 dan RRIC110 menyebabkan terjadinya perubahan pola pita protein lateks dari klon yang sama. Terjadi induksi pembentukan protein baru dengan BM 24 kDa pada kombinasi okulasi PB260/ PR255, BPM1/RRIC100, BPM24/ RRIC100, BPM24/RRIC102 dan BPM24/ RRIC110. Hasil analisis isoenzim pada lateks dan daun batang atas menunjukkan bahwa isoenzim MDH, PGD, PGI, PER, SKD, GOT dan LAP menghasilkan pita yang monomorfik untuk seluruh kombinasi okulasi yang diuji. Polimorfisme EST ditemukan pada PR255/PB260, LCB1320/ PB260, GT1/PB260, BPM24/ RRIC100 dan BPM24/RRIC101. Sedang polimorfisme AP ditemukan pada PR255/ PB260, LCB1320/PB260, GT1/ PB260, BPM24/ RRIC101, BPM24/ RRIC102, dan RRIC100/RRIC110. Polimorfisme untuk MDH dan SKD juga ditemukan pada PR255/PB260, LCB1320/PB260 dan GT1/ PB260. Berdasarkan sidik gerombol dan UPGMA dari penggabungan data analisis SDS-PAGE protein dan isoenzim menunjukkan bahwa batang atas dari klon yang sama yang diokulasikan pada berbagai batang bawah yang berbeda, umumnya berada dalam satu sub kelompok yang sama. Namun tingkat kesamaan genetiknya beragam, hal ini menunjukkan adanya perbedaan pengaruh batang bawah terhadap batang atas yang sama. SummaryThe heterogenity of root stocks leads to stock-scion interactions resulting in considerable variation at different level among the population of a single clone. The aim of this research is to study the effect of several rootstock on scion of the rubber clone, based on the changes on budding patterns of leaf or latex protein and isozymes esterase (EST, acid phosphatase (AP), malat dehydrogenase (MDH), phosphogluco oxaloacetate (PGD), phospho glucose isomerase (PGI), peroxidase (PER), shikimic dehydrogenase (SKD), glutamate oxaloacetate (GOT) and leucyne aminopeptidase (LAP), bands pattern. The combinations stocks/scions tested were (a) scion PB260 clone combined with PR255, BPM1, LCB1320, PR300, AVROS2037, RRIM712 and GT1. Control combinations used were GT1/GT1 and (b) as a scion BPM1, BPM24, RRIC100 dan RRIC102 combined with BPM1, BPM24, RRIC100, RRIC101, RRIC102 and RRIC110. The results showed that latex protein bands pattern of PB 260 as a scion were changed in combination with PR255, BPM1, LCB1320, PR300, AVROS2037, RRIM712 as a rootstocks. BPM1, BPM24, RRIC100, RRIC101, RRIC102 and RRIC110 as a rootstocks caused the changes of the latex protein patterns of BPM1, BPM24, RRIC100, RRIC102 as a scion. The interaction among stock/scion showed by the changes on the levels proteins or the prsence of new proteins with MW 24-63 kDa especially in combination of BPM1/ RRIC100, BPM24/ RRIC100, BPM24/ RRIC102 and BPM24/ RRIC110. BPM1, BPM24, RRIC100, RRIC102 and PB260 in combined with all the stocks were tested. Analyses of leaf and latex isozymes showed that MDH, PGD, PGI, PER, SKD, GOT and LAP produced monomorphic isozyme bands. The polymorphism were found on EST of PR255/PB260, LCB1320/PB260, GT1/PB260, BPM24/RRIC100 and BPM24/ RRIC101. While the combination of PR255/ PB260, LCB1320/ PB260, GT1/ PB260, BPM24/RRIC101, BPM24/ RIC102, and RRIC100/RRIC110 produced AP polymorphism. Polymorphism for MDH and SKD were also found in PR255/ PB260, LCB1320/PB260 and GT1/PB260. Cluster and UPGMA analyses of protein and isozyme pattern showed combinations of a scion with several different rootstocks belong to the same sub group. However, genetic symilarities among individuals were varieties, it showed that the differences effect of rootstock to the scion from the same clone.